Systematic Preformulation Studies and Drug-Excipient Compatibility Evaluation of Abacavir Sulphate for Design of Gastroretentive Floating Drug Delivery System - Verma, Sanatan Kumar; S, Rajasekaran. (Journal of Neonatal Surgery, 2025)
Background: Gastroretentive floating microspheres offer promising approach for sustained delivery of antiretroviral drugs. Comprehensive preformulation studies are essential for rational formulation development and selection of compatible excipients. Objective: To conduct systematic preformulation studies of Abacavir sulphate for development of gastroretentive floating microspheres and evaluate drug-excipient compatibility with selected polymers. Methods: Preformulation studies including organoleptic properties, flow properties (angle of repose, bulk density, tapped density, compressibility index, Hausner ratio), melting point, pH, and solubility were performed as per standard procedures. Drug-excipient compatibility was evaluated by physical observation under accelerated stability conditions (40°C/75%RH and 60°C) and FTIR spectroscopy using HPMC K4M and HPMC K100M polymers. Results: Abacavir sulphate appeared as off-white odorless powder with melting point 165°C. The drug exhibited poor flow properties with angle of repose 29°28", compressibility index 28.04%, and Hausner ratio 1.34. The aqueous solution showed neutral pH (7.5) and drug was freely soluble in water. Compatibility studies revealed no physical changes after one month storage at accelerated conditions. FTIR analysis showed characteristic peaks at 3463.2, 2958.6, 2849.7, 1660.0, and 1451.6 cm⁻¹. No interaction was observed between drug and polymers as all characteristic peaks were retained in mixture spectrum. Conclusion: Preformulation studies confirmed suitability of Abacavir sulphate for gastroretentive microsphere development. The drug showed good compatibility with HPMC K4M and K100M polymers, supporting their use in formulation design